1998
DOI: 10.1038/bjc.1998.280
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of stromal and cancer cell thymidine phosphorylase reactivity in non-small-cell lung cancer: impact on tumour neoangiogenesis and survival

Abstract: Summary Angiogenesis is recognized as an important step in tumour pathogenesis that is related to invasion and metastatic spread and which consequently results in poor clinical outcome. In this study, we have examined the role of tumour stroma-activated fibroblasts and macrophage infiltration in the development of the angiogenic and metastatic phenotype in non-small-cell lung cancer (NSCLC). A total of 141 cases of early stage I-Il NSCLC treated with surgery alone were analysed. The JC-70 (anti-CD31) MAb was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 26 publications
6
78
0
2
Order By: Relevance
“…The role of immune response in cancer progression seems to be possibly dual and remains not well elucidated (Chambers et al, 1997;Jonjic et al, 1998;Koukourakis et al, 1998;Toi et al, 1999;Shimura et al, 2000). Indeed, despite the role of monocytes/ macrophages in host defence, previous studies have suggested a potential deleterious effect of stroma-localised monocytes/macrophage, in relation with enhanced angiogenesis ( Urokinase is visualised as a transparent lysis area of the gel after 36 h. Two lysis areas were observed with purified u-PA, one at 55 kDa molecular weight and a minor one corresponding to the low molecular weight u-PA at 35 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…The role of immune response in cancer progression seems to be possibly dual and remains not well elucidated (Chambers et al, 1997;Jonjic et al, 1998;Koukourakis et al, 1998;Toi et al, 1999;Shimura et al, 2000). Indeed, despite the role of monocytes/ macrophages in host defence, previous studies have suggested a potential deleterious effect of stroma-localised monocytes/macrophage, in relation with enhanced angiogenesis ( Urokinase is visualised as a transparent lysis area of the gel after 36 h. Two lysis areas were observed with purified u-PA, one at 55 kDa molecular weight and a minor one corresponding to the low molecular weight u-PA at 35 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…14 -24 Several investigators 20 -24 have focused on tumor cell-TP expression in NSCLC. In addition, Koukourakis et al 21 reported stromal cell-TP expression and tumor cell-TP expression in NSCLC, indicating that stromal fibroblasts intensively express TP in a number of NSCLCs. Intensive TP expression has been observed in intratumoral macrophages of colorectal, gastric, and breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…TP expression has been observed in tumor cells of nonsmall cell lung carcinoma (NSCLC). 20 -24 Koukourakis et al 21 reported different patterns of stromal and tumor cell-TP expression in NSCLC. The clinicopathologic significance of TP expression in tumor cells and/or stromal cells in NSCLC has remained unclear.…”
mentioning
confidence: 99%
“…We suggest that although hypoxia triggers the expression of a cascade of angiogenic factors through HIF stabilization, the process of angiogenesis is subject to other modulators. Strong expression of endogenous inhibitors of angiogenesis produced by cancer or stromal cells may therefore counter the effectiveness of the angiogenic cascade released by HIFs (Dong et al, 1997;Koukourakis et al, 1998), while a moderate vascularization may be enough for the restoration of oxygenation that may bring the HIF levels close to the normal level. HIF levels are normalized within minutes after the restoration of oxygenation (Wiesner et al, 1998).…”
Section: Hif1α/2α Expression In Nsclc 887mentioning
confidence: 99%